Utilisation and Safety of Deferasirox: Results from an Observational Cohort Study in England - Osborne, Vicki; Davies, Miranda; Layton, Deborah; Shakir, Saad A. W. (Drug safety, 2018)
Introduction Deferasirox (EXJADE ® , Novartis, UK) is an oral iron-chelating agent primarily used to reduce chronic iron overload in patients receiving blood transfusions for various chronic anaemias and some non-transfusion dependant anaemias. Objective The aim of this study was to examine the utilisation and safety of deferasirox used in general practice in England. Method A single exposure observational cohort study design was used. Patients were identified from dispensed prescriptions for deferasirox between September 2006 and September 2014. Outcome data were collected via postal questionnaires sent to prescribers ≥ 6 months after first dispensed prescription for an individual patient. Summary descriptive statistics were calculated. Results The evaluable cohort consisted of 122 patients, of which 41.8% were aged 2–17 years. Frequent reasons for prescribing were sickle cell anaemia (27/103 where specified, 26.2%) and beta thalassaemia (26, 25.2%). The majority of patients (43/51, 84.3%) were prescribed the licensed doses of 10 or 20 mg/kg/day at start. Prior measurements of serum creatinine were only reported for a small proportion this study (18/122, 14.8%). In total, 91 incident events were reported, including two of raised serum creatinine. Conclusion These results show that deferasirox is largely being prescribed for its licensed indications in general practice in England and events reported were consistent with the known safety profile.